Does antenatal care timing influence stillbirth risk in the third trimester? A secondary analysis of perinatal death audit data in South Africa. (26th June 2017) - Lavin, T; Pattinson, RC
Abstract : Objective: To explore stillbirth risk across gestation in three provinces of South Africa with different antenatal care schedules. Design: Retrospective audit of perinatal death data using South Africa's Perinatal Problem Identification Programme. Setting: In 2008, the Basic Antenatal Care Programme was introduced in Limpopo and Mpumalanga provinces, reducing appointments to five visits at booking, 20, 26, 32, 38 weeks and 41 weeks if required. In the Western Cape province seven appointments remained at booking, 20, 26, 32, 34, 36, 38 and 41 weeks if required. Population: All audited stillbirths ( n = 4211) between October 2013 to August 2015 in Limpopo, Mpumalanga and Western Cape. Methods: Stillbirth risk (26–42 weeks of gestation, >1000 g) across gestation was calculated using Yudkin's method. Stillbirth risk was compared between provinces and relative risks were calculated between Limpopo/ Mpumalanga and Western Cape. Main outcome measures: Stillbirth risk across gestation. Results: Stillbirth risk peaked at 38 weeks of gestation in Limpopo (relative risk [RR] 3.11, 95% CI 2.40–4.03, P < 0.001)and Mpumalanga (RR 3.09, 95% CI 2.37–4.02, P < 0.001) compared with Western Cape, where no peak was observed. Stillbirth risk at 38 weeks gestation in Limpopo and Mpumalanga were statistically greater than both the 37 and 39 weeks gestation within provinces ( P < 0.001). As expected, a peak at 41 weeks of gestation was observed in all provinces. Conclusions: The increased period of stillbirth risk occurs after a 6‐week absence of antenatal care. This calls for a refocus on the impact of reduced antenatal care visits during the third trimester. Tweetable abstract: Reduced antenatal care in the third trimester may increase stillbirth risk. Tweetable abstract: Reduced antenatal care in the third trimester may increase stillbirth risk.